Book Review: - Carol Roderick (Grounded Theory Review: An International Journal)
In Children in Genocide: Extreme traumatization and affect regulation (2008), Suzanne Kaplan explores the affects and memories of individuals who have survived extreme traumatization during their childhood, specifically Jewish survivors of the Holocaust and teenagers who survived the genocide in Rwanda in 1994. In the introduction, Kaplan explains that she has aimed to “write a text that can, to the greatest extent possible, convey a fraction of the feeling of what it meant to be a child during a genocide” (Kaplan, 2008, p.1). The majority of the book is devoted to presenting an analysis of the oral life histories of the survivors interviewed. The experiences are organized into three themes: 1) perforating , how the psychic shield is has been perforated by intense trauma; 2) space creating , the inner psychic processes through which the persecuted create mental space helps to survive the psychological damage and trauma; and 3) age distorting , a twisting of time that results in participants not feeling their actual chronological age.